The SEC and Capital Market Regulation : The Politics of Expertise - Khademian, Anne M., 1961- (Book collections on Project MUSE., 1992)
In recent years the U.S. securities markets have been engulfed by crisis. The Dow Jones industrial average now commonly rises and falls to levels unimaginable ten years ago. Investors trade giant portfolios in rapid sequence via computers. Trading in Tokyo, Hong Kong, and London has a growing impact on the New York market. Legal barriers between commercial and investment banking are growing more porous, and Wall Street has been shaken by a series of spectacular scandals. Yet the central U.S. regulator, the Securities and Exchange Commission, remains a relatively obscure and unexamined agency. Anne M. Khademian now addresses its significance for securities policy and uses the agency as a model for the study of bureaucracy and bureaucratic theory. The classic tension within U.S. federal agencies is between the need to hold bureaucrats politically accountable to elected officials and the need to delegate complex decision making to officials with "independent" expertise. In the SEC this tension is especially pronounced because of the agency's dependence on attorneys and economists. Khademian traces the development of a regulatory strategy from the creation of the SEC by Franklin D. Roosevelt in 1934 to the present, examines the role of SEC experts and their political overseers in Congress as they create policy, and evaluates the stability of that policy. Her study shows how the tug-of-war between demands for accountability and giving freedom to expertise has affected the agency's evolution and its regulatory activities. Rather than focusing on the success or failure of political oversight, or the accountability or lack of accountability of an agency to its political overseers, The SEC and Capital Market Regulation examines the interaction of bureaucrats, politicians, and the White House. It connects early debates in the field of public administration with current arguments of rational choice scholars concerning bureaucratic independence. Based on interviews with representatives from the SEC, industry representatives, congressional staff, and former members of Congress, it suggests a new and productive approach to the study of bureaucratic behavior. Not only those interested in securities policy, but also students of public administration, bureaucratic politics, and government regulation will find much of interest in this detailed and insightful study.